1971
DOI: 10.1111/j.1469-8986.1971.tb00449.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Instructional Set and Autonomic Perception on Cardiac Control

Abstract: Fifty‐four Ss were divided into three instructional groups. One group was instructed to increase their heart rate (HR) every time a signal was presented; a second group was told to decrease their HR; and a control group was not instructed to change their HR in any direction. Results indicate that Ss can increase or decrease their HR in the absence of externalized feedback. These HR changes do not appear to be mediated by respiration or skin resistance variations. In addition, Ss were divided into groups on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
3

Year Published

1974
1974
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(17 citation statements)
references
References 7 publications
0
14
3
Order By: Relevance
“…The internal consistency for the scale was α =.89. Furthermore, participants completed the specific form of the APQ (Bergman & Johnson, 1971; Johansson & Öst, 1982) to assess their perception of bodily sensations during the conversation.…”
Section: Methodsmentioning
confidence: 99%
“…The internal consistency for the scale was α =.89. Furthermore, participants completed the specific form of the APQ (Bergman & Johnson, 1971; Johansson & Öst, 1982) to assess their perception of bodily sensations during the conversation.…”
Section: Methodsmentioning
confidence: 99%
“…Bergman and Johnson (1971) used a specific form of the APQ and found that the subjects with medium scores displayed heart-rate control to a larger extent than either high or low scorers. Blanchard et al (1972) gave college students the general form of the APQ 2-3 weeks before the experiment con-sisting of increasing and decreasing the heart rate.…”
Section: Introductionmentioning
confidence: 99%
“…A direct and specific response to the literal meaning of the instructions is not likely, while the intervention of associative imagery is suggested by interview data. Whatever the mechanism, the influence of instructional set on cardiovascular performance in the feedback paradigm has been demonstrated by other data (10)(11)(12)31). Whether mere awareness of the physiologic task at hand influences success has not been studied systematically, to our knowledge.…”
Section: Discussionmentioning
confidence: 89%
“…Such data indicate that instruction, and directional task awareness may play a major confounding role in the assessment of the efficacy of external feedback. Bergman and Johnson (11,12) have explored this question in relation to heart-rate control. Significant changes occurred appropriate to directional instructions in the absence of feedback, while the addition of feedback did not seem to augment the response to instruction.…”
Section: Introductionmentioning
confidence: 98%